Remission of symptoms is not equal to functional recovery: Psychosocial functioning impairment in major depression - Yang, Hao; Gao, Shuzhan; Li, Jiawei; Yu, Haoran; Xu, Jingren; Lin, Chenchen; Yang, Hua; Teng, Changjun; Ma, Hui; Zhang, Ning (Frontiers in Psychiatry, 2022)
The ultimate goal of depression treatment is to achieve functional recovery. Psychosocial functioning is the main component of functional impairment in depressed patients. The concept of psychosocial functioning has an early origin; however, its concept and connotation are still ambiguous, which is the basic and key problem faced by relevant research and clinical application. In this paper, we start from the paradox of symptoms remission and functional recovery, describe the concept, connotation, and characteristics of psychosocial functioning impairment in depressed patients, and re-emphasize its importance in depression treatment to promote research and clinical applications related to psychosocial functioning impairment in depressed patients to achieve functional recovery.